Self-perceived barriers to healthcare access for patients with post COVID-19 condition - Iris M. Brus; Inge Spronk; Suzanne Polinder; Alfons G. M. Olde Loohuis; Peter Tieleman; Stella C. M. Heemskerk; Sara Biere-Rafi; Juanita A. Haagsma (BMC, 2024)
Abstract Background Many patients with post COVID-19 condition (PCC) require healthcare services. However, qualitative studies indicate that patients with PCC encounter many barriers to healthcare access. This cross-sectional study aimed to determine how many PCC patients report barriers to healthcare access and which barriers are reported, and to explore differences between subgroups. Methods Data were collected via an online survey from 10,462 adult patients with a confirmed or suspected COVID-19 infection in the Netherlands, who experienced persisting symptoms ≥ 3 months after the initial infection. To study self-perceived barriers, a list of eleven possible barriers was used, covering multiple aspects of healthcare access. Differences between subgroups based on sociodemographic characteristics, medical characteristics, PCC symptoms (fatigue, dyspnoea, cognitive problems, anxiety and depression), and healthcare use (general practitioner, paramedical professional, medical specialist, occupational physician and mental health professional) were studied through multivariable multinomial (0 vs. 1 vs. > 1 barrier) and binomial regression analyses (for each individual barrier). Results A total of 83.2% of respondents reported at least one barrier to healthcare access. Respondents reported a median of 2.0 (IQR = 3.0) barriers. The barriers "I didn't know who to turn to for help" (50.9%) and "No one with the right knowledge/skills was available" (36.8%) were most frequently reported. Respondents with younger age, higher educational level, not hospitalized during acute COVID-19 infection, longer disease duration, who had more severe PCC symptoms, and who did not consult an occupational physician or paramedical professional, were more likely to report barriers. Analyses per barrier showed that women were more likely to report financial and help-seeking barriers, while men were more likely to report barriers related to availability of care. Hospitalized respondents were less likely to report barriers related to availability of care, but not less likely to report financial or help-seeking barriers. Conclusions This study shows that the majority of patients with PCC experiences barriers to healthcare access. Particular attention should be paid to younger, non-hospitalized patients with a long disease duration and severe PCC symptoms. Efforts to remove barriers should focus not only on improving availability of care, but also on helping patients navigate care pathways.